Effect of duration and pressure of carbonation curing on the chloride profile in concrete - Roberto Luiz Dias; Neusa Aparecida Munhak Beltrame; Jordi Rius Gonzalez; Ronaldo Alves Medeiros-Junior (Revista IBRACON de Estruturas e Materiais)
Abstract Carbonation curing alters the characteristics of the concrete's microstructure and can interfere with the penetration of aggressive ions. The objective of this article was to evaluate the influence of CO2 pressure and carbonation cure time on chloride profiles. Concrete specimens were cured by carbonation with CO2 pressures ranging from 5 to 25 Psi, for a time within the carbonation chamber of 8, 24, and 36 hours. These concretes were subjected to 30 wetting and drying cycles in NaCl solution to stimulate the chloride ingress. The carbonation depth and the microstructure of the concrete were monitored over time. Chloride profiles were obtained and modeled by 4 mathematical equations. The results showed that the combination of less time and CO2 pressure during carbonation curing potentiated the reduction of chloride penetration in concrete. Also, the carbonation curing conditions of 5 and 10 Psi for 8 hours reduced the chloride diffusion coefficient.